Impact of Early Weight-Bearing Following Ankle Arthroscopy and Microfracture of Talar Osteochondral Defects. Issue 4 (16th October 2019) - Lefebvre, Thomas; Scott, Daniel J.; Peterson, Jonathan; Adams, Samuel; Amendola, Annunziato
Category: Arthroscopy Introduction/Purpose: Ankle impingement and ankle osteochondral defects are common problems seen by foot and ankle specialist that often go on to require surgical managment. After conservative treatment fails, ankle impingement is often managed by arthroscopic debridement, whereas ankle OCDs are often treated with ankle arthroscopy and microfracture as a first line treatment. However, surgeons have various treatment protocols post-operatively after these procedures, with some surgeons allowing immediate weight bearing, were as other surgeons restrict patients weight bearing. There is similar heterogeneity in the manner of immobilization post-operatively. The purpose of this study is to retrospectively review the outcomes of patients undergoing ankle arthroscopy and micro fracture, to determine if immediate weight bearing or removable immobilization had any impact on outcomes. Methods: We retrospectively reviewed 79 patients at our institution who underwent ankle arthroscopy with microfracture for talar osteochondral defects over 3 years. This included surgeries performed by one of 7 fellowship trained foot and ankle surgeons at our institution. Each surgeon had different protocols for post-operative weight bearing and immobilization, allowing for a comparison of various post-operative protocols. Patient outcomes were reviewed pre-operatively and post-operatively including age, sex, comorbidities, etiology of talar pathology, post-operative weight bearing status, time to first weight bearing, as well as method and length of immobilization, VAS scores, range of motion, and complications. Clinical outcomes such as time to return to work and return to sport were also evaluated. Results: The average patient age was 38. 42 patients (53%) had an additional procedure performed at the time of ankle arthroscopy and microfracture. There was no significant difference in the average pre-op and post-op VAS or range of motion between the immediate weight bearing group and the delayed weight bearing group. There was interestingly a trend towards lower VAS scores in the immediate weight bearing group (1.4 vs 2.6). Conclusion: Following ankle arthroscopy and microfracture, we found no difference in VAS, range of motion, or complications when allowing immediate, full weight bearing as well as using removable immobilization as compared to a variety of other protocols at early follow up. In fact, there was a trend towards lower VAS scores in the immediate full weight bearing group. Though this study has early follow up, it does suggest at least the equivalency of allowing immediate weight bearing and removable immobilization following ankle arthroscopy and talar microfracture.